A study on the prediction of the effective diffusivity of gas through porous media from the pore structure - Amorsolo, Alberto V. (1987)
The effective diffusivity of gas through various types of porous media ranging from carbons (metallurgical and formed code, electrode graphite and densse graphite) to hydrogen-reduced sponge iron and glass filter was predicted from three equations derived from the random pore model, the parallel pore model and the ideal pore structure model. Pore structure data used in the three prediction equations were the total void fraction, the fraction of connected macropores, the average effective pore radius and the relative Darcy permeability constant. Results showed that the experimental De values agreed well with the predicted values using any of the models cited for the glass samples. For the other materials investigated, the agreement was not as good, most probably due to the presence of micropores and other pore shapes not considered by the models.
Thesis (M.S. Metallurgical Engineering)--University of the Philippines, Diliman.
Typescript.
Keywords: Diffusion; Porous materials